Surgical treament of chronic pancreatitis (literature review) - S. V. Morozov; V. B. Rumyantsev; A. I. Lobakov; A. N. Shcherbyuk; P. B. Flegontov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Target. To summarize the available literature data on the methods of surgical treatment of chronic pancreatitis, evaluate their results, identify shortcomings and possible solutions.Materials and Methods. We conducted a literature review of scientific papers over the past 20 years, using the resources of the search engines PubMed, Cyberleninka and eLIBRARY, on the available methods of surgical treatment of chronic pancreatitis. For this meta-analysis, we used articles containing an evidence-based experimental and clinical base on issues related to long-term and immediate results of surgical treatment.Results and discussion. We analyzed the immediate and long-term results of the methods of surgical treatment of chronic pancreatitis. In almost all studies, resection-drainage methods made it possible to effectively stop the pain syndrome for a long time. However, exoand endocrine insufficiency in most cases persisted or progressed, regardless of the method used. Another disadvantage of the existing methods was the inability to stop bleeding from the area of pancreatojejunostomy in the early postoperative period, so mortality after the development of these complications ranged from 5 to 60%.Conclusion. Based on the results studied, we identified the following disadvantages of the known methods of surgical treatment of chronic pancreatitis: 1. A long loop of the small intestine, at least 70 cm, turned off from digestion, leading to a significant decrease in the length of the intestinal tube, and, accordingly, the area of absorption of food nutrients. 2. The features of the reconstructive stage of the operation do not provide the physiological flow of pancreatic secretion into the duodenum and, accordingly, the activation of enzymes, thereby turning off the duodenal phase of digestion. 3. Roux-enabled loop of the small intestine creates favorable conditions for the development of excessive bacterial growth. 4. Lack of endoscopic evaluation of the pancreas to stop bleeding in the early postoperative period. After analyzing the literature data, we came to the conclusion that the elimination of these shortcomings will improve the results of chronic pancreatitis treatment.